Tonicity-Responsive Enhancer-Binding Protein Mediates Hyperglycemia-Induced Inflammation and Vascular and Renal Injury - Choi, Soo Youn; Lim, Sun Woo; Salimi, Shabnam; Yoo, Eun Jin; Lee-Kwon, Whaseon; Lee, Hwan Hee; Lee, Jun Ho; Mitchell, Braxton D; Sanada, Satoru; Parsa, Afshin; Kwon, Hyug Moo (Journal of the American Society of Nephrology, 2018)
Diabetic nephropathy (DN) has become the single leading cause of ESRD in developed nations. Bearing in mind the paucity of effective treatment for DN and progressive CKD, novel targets for treatment are sorely needed. We previously reported that increased activity of tonicity-responsive enhancer-binding protein (TonEBP) in monocytes was associated with early DN in humans. We now extend these findings by testing the hypotheses that TonEBP in macrophages promotes hyperglycemia-mediated proinflammatory activation and chronic renal inflammation leading to DN and CKD, and TonEBP genetic variability in humans is associated with inflammatory, renal, and vascular function-related phenotypes. In a mouse model of DN, compared with the wild-type phenotype, TonEBP haplodeficiency associated with reduced activation of macrophages by hyperglycemia, fewer macrophages in the kidney, lower renal expression of proinflammatory genes, and attenuated DN. Furthermore, in a cohort of healthy humans, genetic variants within TonEBP associated with renal function, BP, and systemic inflammation. One of the genetic variants associated with renal function was replicated in a large population-based cohort. These findings suggest that TonEBP is a promising target for minimizing diabetes- and stress-induced inflammation and renovascular injury.